The Effect of Atmospheric Cold Plasma on Bacterial Stress Responses and Virulence Using Listeria monocytogenes Knockout Mutants - Patange, Apurva; O’Byrne, Conor; Boehm, Daniela; Cullen, P. J.; Keener, Kevin; Bourke, Paula (Frontiers in Microbiology, 2019)
Listeria monocytogenes is an opportunistic intracellular pathogen commonly associated with serious infections and multiple food-borne outbreaks. In this study, we investigated the influence of Atmospheric cold plasma (80 kV, 50 Hz) on L. monocytogenes (EGD-e) and its knockout mutants of sigB, rsbR, prfA, gadD and lmo 0799 genes at different treatment time intervals. Further, to ascertain if sub-lethal environmental stress conditions could influence L. monocytogenes survival and growth responses, ACP resistance was evaluated for the cultures exposed to cold (4 °C) or acid (pH 4) stress for 1 h. The results demonstrate that both wild-type and knockout mutants were similarly affected after 1 min of plasma exposure (p > 0.05), with a difference in response noted only after 3 min of treatment. While all L. monocytogenes strains exposed to acid/cold stress were hypersensitive to ACP treatment and were significantly reduced or inactivated within 1 min of treatment (p < 0.05). The results indicate sigB and prfA are important for general stress resistance and biofilm respectively, loss of these two genes significantly reduced bacterial resistance to ACP treatment. In addition, exposure to sub-lethal 1min ACP increased the gene expression of stress associated genes. SigB showed the highest gene expression, increasing by 15.60 fold, followed by gadD2 (7.19) and lmo0799 (8.6) after 1 min exposure. Overall, an increase in gene expression was seen in all stress associated genes analyzed both at 1 min treatment; while long treatment time reduced the gene expression and some cases down-regulated prfA and gadD3 gene expression. By comparing the response of mutants under ACP exposure to key processing parameters, the experimental results presented here provide a baseline for understanding the bacterial genetic response and resistance to plasma stress and offers promising insights for optimizing ACP applications.